The paracrine control of vascular motion. A historical perspective. (November 2016) - Nava, Eduardo; Llorens, Silvia
Graphical abstract: Abstract: During the last quarter of the past century, the leading role the endocrine and nervous systems had on the regulation of vasomotion, shifted towards a more paracrine-based regulation. This begun with the recognition of endothelial cells as active players of vascular control, when the vessel's intimal layer was identified as the main source of prostacyclin and was followed by the discovery of an endothelium-derived smooth muscle cell relaxing factor (EDRF). The new position acquired by endothelial cells prompted the discovery of other endothelium-derived regulatory products: vasoconstrictors, generally known as EDCFs, endothelin, and other vasodilators with hyperpolarizing properties (EDHFs). While this research was taking place, a quest for the discovery of the nature of EDRF carried back to a research line commenced a decade earlier: the recently found intracellular messenger cGMP and nitrovasodilators. Both were smooth muscle relaxants and appeared to interact in a hormonal fashion. Prejudice against an unconventional gaseous molecule delayed the acceptance that EDRF was nitric oxide (NO). When this happened, a new era of research that exceeded the vascular field commenced. The discovery of the pathway for NO synthesis from L-arginine involved the clever assembling of numerous unrelated observations of different areas of knowledge. The last ten years of research on the paracrine regulation of the vascular wall has shifted to perivascular fat (PVAT), which is beginning to be regarded as the fourth layer of the vascular wall. Starting with the discovery of an adipose-derived relaxing substance (ADRF), the role that different adipokines have on the paracrine control of vasomotion is now filling the research activity of many vascular pharmacology labs, and surprising interactions between the endothelium, PVAT and smooth muscle are being unveiled.